1998
DOI: 10.1177/002224299806200206
|View full text |Cite
|
Sign up to set email alerts
|

Employee Behavior in a Service Environment: A Model and Test of Potential Differences between Men and Women

Abstract: The authors examine the attitudes and behaviors of employees who provide frontline service and address the extent to which relationships vary among male and female employees. The overall model predicts effects of role stress and work/nonwork conflict on customer-contact employees’ job performance, job and life satisfaction, and quitting intent. Results of structural equations modeling suggest an important role for work/nonwork conflict overall as well as two areas of interesting variation across gender. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
266
2
10

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(288 citation statements)
references
References 58 publications
10
266
2
10
Order By: Relevance
“…Bagozzi (1980) found that job performance influenced job satisfaction, which has been empirically supported in other studies (e.g., Behrman & Perrault, 1984;Dubinsky & Hartley, 1986;Lusch & Serpkenci, 1990;Singh, 1993). Babin and Boles (1998) argued that the relationship between job performance and job satisfaction has been positive but modest in empirical studies. Bagozzi (1978Bagozzi ( , 1980 has studied the relationship between performance and satisfaction the most extensively.…”
Section: Job Performance Job Satisfaction and Role Stressmentioning
confidence: 60%
See 3 more Smart Citations
“…Bagozzi (1980) found that job performance influenced job satisfaction, which has been empirically supported in other studies (e.g., Behrman & Perrault, 1984;Dubinsky & Hartley, 1986;Lusch & Serpkenci, 1990;Singh, 1993). Babin and Boles (1998) argued that the relationship between job performance and job satisfaction has been positive but modest in empirical studies. Bagozzi (1978Bagozzi ( , 1980 has studied the relationship between performance and satisfaction the most extensively.…”
Section: Job Performance Job Satisfaction and Role Stressmentioning
confidence: 60%
“…The rationale is that a common response to increased role stress has shown to be withdrawal from the organization. This response, however, results from low job satisfaction rather than directly from high role stress (Ashforth & Saks, 1996;Babin & Boles, 1998;Baroudi, 1985). The majority of studies (e.g., Kemery, Mossholder, & Bedeian, 1987) indicate that "withdrawal" is a natural reaction to low job satisfaction caused by high role stress.…”
Section: Role Stress Satisfaction and Withdrawalmentioning
confidence: 99%
See 2 more Smart Citations
“…The dependent variable, perceived job performance, was adopted from Babin and Boles (1998). It consisted of 7 self-reported items on a 7-point Likert scale, ranging from "1" for strongly disagree to "7" for strongly disagree.…”
Section: Methodsmentioning
confidence: 99%